Direction Finding Using a Four-Ray Street Canyon Propagation Model in Presence of Periodic Lamp-Posts for Use in Microcellular Wireless Communication and Angular Estimation - Sarah Poormohammad; Forouhar Farzaneh (IEEE Access)
A four-ray street canyon model, including the polarization effect, is considered as the basic propagation model and an array of the periodic lampposts is added within the scenario. Using the MUISC (Multiple Signal Classification) direction-finding algorithm the angle of arrival to the access point is computed in both azimuth and elevation. Through this, the root mean square errors of DOA are estimated in both azimuth and elevation. It is demonstrated that the presence of the lampposts increases significantly the angle of arrival estimation errors. The evolution of the errors is computed by moving the mobile set along and across the street. The channel angular spread is computed and through Monte-Carlo simulations the mean and the standard deviation of the angular spread are computed both azimuth and the elevation domains. Monte-Carlo simulations were used to evaluate the root mean square errors. The resulting values are compared to the 3GPP TR 38.901 measurement model and a relatively good agreement is observed. The method could be used in microcellular wireless communication systems for angular estimation. The main point of this work is the combination of the lampposts with a four-ray street canyon model which gives in results which are near to a real propagation scenario.